Pengolahan Air Parit Sungai Jawi dengan Sistem Konvensional - Arditya, Muhammad Kevin; Sinaga, Hanna Dewi; Narazarezcova, Brigitta Pamella; Purnaini, Rizki (Jurnal Teknologi Lingkungan Lahan Basah, 2024)
The distribution of clean water that has not been carried out thoroughly in several areas has caused some communities to have no access to clean water supplies. Based on this, we need a water treatment technology that can be done by the community so that the community can obtain clean water by utilizing water sources in the surrounding area. This research aims to design a water treatment tool for the Jawi River ditch into clean water and to know the effectiveness of the device design in reducing the concentration of color, turbidity, and BOD. The method used in this research is quantitative descriptive methods and experiment methods. Meanwhile, the experiment method did by processing the water of the Jawi River ditch into clean water in the field through a water treatment tool made by itself. This research determined that the efficiency of reducing turbidity can reach 46.1%, color reach 61.36%, and BOD can reach 78.9%. However, there are still no parameters that meet the clean water quality standards.